The influence of quality indicators on changes in the color of sour cherry and sweet cherry fruits - Vasylyshyna, O. (Scientific Progress & Innovations, 2024)
The article is devoted to the influence of the main indicators of the ripeness of stone fruits of sour cherries and sweet cherries on the formation of the quality and content of biologically active substances. Sour cherry and sweet cherries have a rich chemical composition due to the presence of sugar, organic acids, phenolic compounds, anthocyanins, quercetin, vitamins C, carotenoids and are considered dietary products. Harvesting fruits at the optimal degree of ripeness is the main indicator that affects quality, transportation, storage and processing. It has been established that the physical and mechanical composition of sour cherry and sweet cherry fruits varies and depends on the indicators of color, optical density, light transmission coefficient. According to research results, the optical density of cherry fruits is 0.30–0.42 % and is inversely dependent on the light transmission coefficient. Fruit density is determined by the influence of growing conditions during the years of research: the highest in 2021 – 0.42 and 0.37 %, and the lowest – in 2023 (0.33 and 0.28 %). In sour cherry fruits, it is higher than in sweet cherries by 0.37 and 0.32 % and is inversely related to the light transmission coefficient. The color of sour cherry and sweet cherry fruits determines their antioxidant activity. Antioxidant activity is the main indicator that determines the quality of sour cherry and sweet cherry fruits and depends on the content of biologically active compounds: phenolics, flavonoids and anthocyanins. According to the results of research, the antioxidant activity of sour cherries exceeds that of sweet cherries by 10–16 %. In 2021, the activity of sour cherry and sweet cherry fruit was 38 % higher than the fruit of 2023, which is due to the influence of growing weather conditions. Thus, the quality of sour cherry and sweet cherry fruits is determined by indicators of antioxidant activity, optical density (0.30–0.42 %) and light transmission coefficient (0.28–0.42 %). The prospect of further research is to establish the relationship between indicators of antioxidant activity and the color of cherry fruits (optical density, light transmission coefficient), which will make it possible to predict the quality of products.